The role of feedback from the school leader during teacher evaluation for teacher and school improvement. Issue 1 (2nd January 2017) - Tuytens, Melissa; Devos, Geert
Abstract: Since the turn of the century, teacher evaluation has been introduced around the world with the intent to improve teaching. However, in the literature on teacher evaluation, often findings reveal critical accounts about the effectiveness of feedback in teacher evaluation for teacher and school improvement. This article presents a qualitative study in eight schools where teachers did indicate to find the feedback they discussed with school leaders during teacher evaluation processes useful. In this study, we investigate whether we can identify what teachers actually do with this feedback and which factors contribute to their response. Our findings demonstrate the importance of school organizational characteristics and an integrated leadership approach for the feedback response of teachers. Also, our findings reveal how teacher evaluation is used in these schools to further school improvement.